P2Y12 inhibitors - Collet, J.-P.; Montalescot, G. (Hämostaseologie, 2009)
The P2Y12 receptor has proven to be a key target in the prevention of complications associated with atherosclerotic vascular disease especially in the context of acute coronary syndrome and percutaneous coronary intervention in addition to aspirin. Three generationsof thienopyridines, ticlopidine, clopidogrel, and prasugrel have proven efficacy in the prevention of ischemic vascular events but with increased bleeding. The concept of individualized tailored therapy has recently emerged with the discovery of the diminished effect of some thienopyridine among carriers of the loss-of-function cytochrome (CYP) P4502C19*2 variant. Non-thienopyridine P2Y12 antagonists have also recently demonstrated that these benefits are not limited to one class of agents or may be generalizable to reversible antagonists of this receptor. Future rational use of these agents will require attention to disease and patient features to strike the optimal balance of benefit to risk.
Keywords: P2Y12 receptors; thienopyridines; platelet; thrombosis; acute coronary syndrome